A local perspective: the women's movement and citizenship, Croydon 1890s–1939. Issue 6 (18th September 2020) - Davidson, Ruth
ABSTRACT: This article will explore the lives of women active in local politics and associational life in Croydon County Borough between the 1890s and 1939. It will argue that a local perspective can reveal the personal, social and political networks that facilitated women's more expansive public roles. It will note the circumstances which enabled them to assert their citizenship rights and duties and consider how women's activism developed in the Borough after 1918. It will argue for the importance of context, spatial and chronological, in the formation of political identities and the on-going resonance of these influences in shaping the local women's movement.